EVALUASI PERATURAN DAERAH NOMOR 02 TAHUN 2011 TENTANG PENGELOLAAN SAMPAH DI KOTA SAMARINDA - La Uje; Nur Fitriyah; Enos Paselle (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and evaluate the Regional Regulation No.02 of 2011 on waste management in the city of Samarinda. The type of this research is descriptive qualitative study, with the main location of research in Sanitation Department Samarinda supported with research sites in four District of the District of Samarinda City, Smaarinda Ilir, North Samarinda and Sungai Kunjang. Primary data derived from interviews with selected informants, as well as from direct observation in the study area. While secondary data derived from data held by the agency. Analysis of the data used in this study is Interaktif model analysis developed by Miles, Huberman, dan Saldana.